2021
DOI: 10.3390/molecules26113212
|View full text |Cite
|
Sign up to set email alerts
|

Bertholletia excelsa Seeds Reduce Anxiety-Like Behavior, Lipids, and Overweight in Mice

Abstract: Overweight, obesity, and psychiatric disorders are serious health problems. To evidence the anxiolytic-like effects and lipid reduction in mice receiving a high-calorie diet and Bertholletia excelsa seeds in a nonpolar extract (SBHX, 30 and 300 mg/kg), animals were assessed in open-field, hole-board, and elevated plus-maze tests. SBHX (3 and 10 mg/kg) potentiated the pentobarbital-induced hypnosis. Chronic administration of SBHX for 40 days was given to mice fed with a hypercaloric diet to determine the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Regarding medicinal plants and their bioactive metabolites, a non-polar fraction of Tilia americana containing the terpene beta-sitosterol and a mixture of fatty acids produced anxiolytic-like effects in rodents [12]. In agreement with this report, a non-polar fraction of Bertholletia excelsa seeds, highly enriched with oleic acid (59.97%) and palmitic acid (21.42%), also produced significant anxiolytic-like effects in mice [10]. All these data together suggest that natural products are a source of several fatty acids with possible anxiolytic properties [13].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding medicinal plants and their bioactive metabolites, a non-polar fraction of Tilia americana containing the terpene beta-sitosterol and a mixture of fatty acids produced anxiolytic-like effects in rodents [12]. In agreement with this report, a non-polar fraction of Bertholletia excelsa seeds, highly enriched with oleic acid (59.97%) and palmitic acid (21.42%), also produced significant anxiolytic-like effects in mice [10]. All these data together suggest that natural products are a source of several fatty acids with possible anxiolytic properties [13].…”
Section: Introductionsupporting
confidence: 86%
“…A meta-analysis reported that polyunsaturated fatty acids, such as Omega-3, produced anxiolytic effects in humans [8]. Similarly, preclinical studies had shown reduced anxiety-like behavior when rodents were treated with a mixture of long-chain saturated fatty acids [9][10][11]. Regarding medicinal plants and their bioactive metabolites, a non-polar fraction of Tilia americana containing the terpene beta-sitosterol and a mixture of fatty acids produced anxiolytic-like effects in rodents [12].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that HDL‐c levels were increased in the supplemented groups, which might be due to high content (approximately 75%) of unsaturated fatty acids in BN because polyunsaturated fatty acids can decrease Apo B levels, whereas monounsaturated fatty acids can increase Apo A1 levels, a protein involved in lipid metabolism (Silva Figueiredo et al, 2017). BN, a source of omega‐3, could modulate antioxidant and anti‐atherosclerotic pathways, as animals supplemented with this nut showed decreased lipid peroxidation and improved lipid profile, represented by higher levels of HDL‐c (Balakrishnan et al, 2019; Carracedo et al, 2019; Frausto‐Gonzalez et al, 2021). Previous data on BN supplementation also found similar results of HDL‐c levels.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the supplemented groups exhibited different responses of adipose tissue parameters; the BN5 group showed an increase in diameter and decrease in density of adipocytes, whereas the BN10 group showed a decrease in diameter and an increase in density. Frausto‐Gonzalez et al (2021) administered BN extracts for 40 days to Swiss‐Webster mice fed a hypercaloric diet, and they observed EAT modulation, indicated by a reduced adipocyte area in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we performed ROC analysis to compare HAMA and TC as factors that distinguish suicidal and non-suicidal individuals. Overweight and obesity have been reported as risk factors for anxiety 37 .…”
Section: Socio-demographic and Clinical Characteristicsmentioning
confidence: 99%